On the three-dimensional CR-submanifolds of the six-dimensional sphere - M. A. Bashir (International Journal of Mathematics and Mathematical Sciences)
We show that the six-dimensional sphere does not admit three-dimensionel totally umbilical proper CR-submanifolds.